The Role of Job Satisfaction as a Mediation between Leadership and Compensation for the Motivation of the National Police - Hakim, Lukmanul; Tamzis; M. Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of leadership and compensation on work motivation with job satisfaction as a mediating variable in personnel of the Lampung Police Human Resources Bureau. The problems raised focus on low work motivation triggered by dissatisfaction with the leadership style and the compensation system that is perceived to be unfair. The novelty of this study lies in the use of a mediation model that places job satisfaction as a link between leadership variables and compensation for motivation, which is rarely comprehensively studied in police settings. The research approach used was quantitative with a census method of 119 respondents, analyzed using path analysis techniques through the help of SPSS and PLS-SEM software. The results showed that leadership and compensation significantly affected job satisfaction, which in turn had an impact on increased work motivation. In addition, job satisfaction has been shown to be an effective mediating variable in the relationship between leadership and compensation for work motivation. This research contributes to the development of public sector human resource management, especially in law enforcement agencies, by emphasizing the importance of job satisfaction as a strategy to increase personnel motivation. Keywords: Leadership, Compensation, Job Satisfaction, Motivation, Policing